Existential Definition at the End of the American Road: Zabriskie Point (1970), Vanishing Point (1971), The Gauntlet (1977) - Ward, James J (Review of International American Studies, 2021)
This article discusses three films that helped landmark American cinema in the 1970s. Although differing in inception and reception, all three belong loosely to the genre of the road movie and are linked by protagonists whose stances of rebellion and alienation were characteristic of the counterculture of the 1970s and by the broader theme of existential self-definition that still influences moviemaking today. A critical and commercial failure on its release in 1970, Michelangelo Antonioni’s Zabriskie Point has been revalorized as an ambitious attempt to represent the political and cultural conflicts that seemed to be fracturing American society at the time. In contrast, Richard Sarafian’s Vanishing Point soon overcame the disadvantage of studio disinterest and established itself as a cult favorite. Arguably the definitive anti-hero of 1970s cinema, the amphetamine-fueled renegade driver played by Barry Newman achieves iconic stature through an act of defiant self-destruction that still leaves viewers of the film stunned. Finally, Clint Eastwood’s The Gauntlet, in which the actor-director breaks with his ‘Dirty Harry’ persona to depict a burned-out cop who redeems a ruined career, and enables himself a new start, not by making his own law but by enforcing the law on the books, and against all odds. In all three films, the still unspoiled landscape of the American Southwest, crisscrossed by its skein of highways, provides the tableau for escapist fantasies that may in fact be real, for high-speed chases and automotive acrobatics that defy the laws of physics, and for vignettes of an ‘outsider’ way of life that was already beginning to perish.